PELATIHAN PENYUSUNAN KUIS INTERKATIF MENGGUNAKAN CANVA BAGI GURU - Yuwono, Muhammad Ridlo; Tasari; Syaifuddin, M. Wahid; Sungkono, Joko; Yuliana; Firmansah, Fery; Wijayanti, Septiana; Retnowati, Niken (LPPM Universitas Widya Dharma Klaten, 2026)
The purpose of this community service activity is to provide teachers with skills to be able to create interactive quizzes using Canva templates and AI Canva through training. The community service team invited Muhammadiyah Plus Middle School, North Klaten, to collaborate in carrying out this activity. The method used in this community service activity was face-to-face training which was held on July 26, 2025. Participants were asked to complete assignments given by the community service team which were collected via Google Drive at the end of the training activity. The results of this training activity were that the training participants were able to create interactive quizzes using templates available in Canva and were able to automatically create interactive quizzes using AI Canva according to the desired prompts according to the subjects they were studying.).